Extensão como meio de ressignificação da Universidade (Participação, 2023)
PARTICIPAÇÃORevista do Decanato de Extensãoda Universidade de Brasília Ano 23 - No 39 - Julho/2023ISSN 1677-1893Periodicidade: Semestral Tiragem: DigitalUNIVERSIDADE DE BRASÍLIAReitoraMárcia Abrahão MouraVice-ReitorEnrique Huelva UnternbäumenDecano de AdministraçãoAbimael de Jesus Barros CostaDecano de Assuntos ComunitáriosIleno Izídio da CostaDecano de Ensino de GraduaçãoDiêgo Madureira de OliveiraDecana de ExtensãoOlgamir AmanciaDecano de Pós-GraduaçãoLucio Remuzat Rennó JuniorDecana de Pesquisa e InovaçãoMaria Emilia Machado Telles Walter Decana de Gestão de PessoasMaria do Socorro Mendes GomesDecana de Planejamento, Orçamentoe Avaliação InstitucionalDenise ImbroisiDECANATO DE EXTENSÃODiretoria de Desenvolvimentoe Integração Social (DDIS) Rogério Ferreira (Diretor)Diretoria Técnica de Extensão (DTE)Alexandre Pilati (Diretor)Diretoria de Difusão Cultural (DDC) Flávia Narita (Diretora)EDITORIAL Editor Científico Prof. Dr. Rogério Ferreira (DEX/UnB)Edição e OrganizaçãoIsadora Vergara (UnB)Guilherme Alves (UnB)Projeto Gráfico e Diagramação:Luís Henrique da Silva Menezes (UnB)Revisão de TextoGuilherme Alves (UnB)CapaLuís Henrique da Silva Menezes (UnB)CONTATOTelefone: (61) 3107-0315Campus Universitário Darcy RibeiroPrédio da Reitoria, 2 piso, Sala B1-42CEP: 70910-900. Brasília, DF.www.dex.unb.brSEER: http://periodicos.bce.UnB.br/index.php/participacao/index e-mail: revistaparticipacao@gmail.com